Development and Pilot Study of Group-Based Dietary Self-Management Program for Community Dwellers with Hypertension - Ridwan, Arfiza; Boonyasopun, Umaporn; Jittanoon, Piyanuch (Department of Nursing, Faculty of Medicine, Diponegoro University, 2012)
Background: In most countries worldwide, hypertension is considered as an important problem. Moreover, an increasing trend in the prevalence and incidence has been reported in most countries. This increasing trend requires an innovative approach to improve the lifestyle modification of hypertensive sufferers including their dietary behaviors. Objective: This developmental research aims to develop a program for improving the dietary behaviors of community dwellers with hypertension. Method: The process of this program development includes a literature review related to the self-management programs for hypertension, and dietary behavior outcomes, expert validation, and pilot testing. Result: The setting, strategies, duration, and outcome measurement from the literature review were taken into consideration to develop the new program. The newly developed group-based self-management program consists of: 1) the sharing and reflecting of individual current dietary behavior, 2) group educational session, 3) individual comparison of behavior and reflection of obstacles, 4) individual goal setting, and 5) follow up. In the educational session, the DASH eating plan is used as the reference as it is commonly used in studies about diet for hypertension. Key words: hypertension, self-management, group based program, dietary behaviors.